2001
DOI: 10.1046/j.1365-3156.2001.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Dengue transmission risk maps of Argentina

Abstract: SummaryDengue is an emerging disease that has become important in Argentina because of its vector's presence (Aedes aegypti) and its endemicity in neighbouring countries. Thematic maps were built for Argentina considering four main factors: population susceptibility to dengue virus infection (population density); entrance of the virus from endemic countries (main roads and airports); conditions for the vector (urbanization, altitude, minimum, maximum and mean daily temperatures) and virus extrinsic incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 13 publications
(16 reference statements)
0
48
0
2
Order By: Relevance
“…The introduction of DENV in Córdoba city and the occurrence of Based on a previous study, the survival of Ae. aegypti in Argentina was estimated to be 15 days (Carbajo et al 2001), then autochthonous dengue transmission might be expect to be limited by RND values higher than fifteen. At higher values, virus extrinsic incubation period could not be completed before mosquito death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of DENV in Córdoba city and the occurrence of Based on a previous study, the survival of Ae. aegypti in Argentina was estimated to be 15 days (Carbajo et al 2001), then autochthonous dengue transmission might be expect to be limited by RND values higher than fifteen. At higher values, virus extrinsic incubation period could not be completed before mosquito death.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low levels of immunization in Argentina (Carbajo et al 2001), and the low number of autochthonous dengue cases registered in a highly populated area like Córdoba city, …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that GIS is an effective tool for the delineation of areas at increased risk of vector-borne disease outbreaks, including Lyme disease (Nicholson & Mather 1996) and malaria (Martin et al 2002). Additionally, dengue risk maps have been developed using GIS at the global scale (Hopp & Foley 2003), as well as for Argentina (Carbajo et al 2001) and New Zealand (de Wet et al 2001). Finally, Napier (2003) developed a risk model and map for Hawaii using GIS with a different approach and different variables than those included here.…”
Section: Methodsmentioning
confidence: 99%
“…The increasing transmission of dengue in Brazil, Bolivia and Paraguay has been related to epidemics in Northern Argentina 2 . Misiones, Formosa and Salta have been the most affected provinces and are located in high-risk zones for dengue transmission in Argentina 2 . In the absence of a vaccine and clinical cures, control of dengue will continue to depend on the reduction of Aedes aegypti populations and mosquito interactions with humans.…”
Section: Introductionmentioning
confidence: 99%